Why so Few, Still? Challenges to Attracting, Advancing, and Keeping Women Faculty of Color in Academia - Fox Tree, Jean E.; Vaid, Jyotsna (Frontiers in Sociology, 2022)
From its earliest beginnings, the university was not designed for women, and certainly not for women of color. Women of color in the United States are disproportionately under-represented in academia and are conspicuous by their absence across disciplines at senior ranks, particularly at research-intensive universities. This absence has an epistemic impact and affects future generations of scholars who do not see themselves represented in the academy. What are the barriers to attracting, advancing, and retaining women faculty of color in academia? To address this question we review empirical studies that document disparities in the assessment of research, teaching, and service in academia that have distinct implications for the hiring, promotion, and professional visibility of women of color. We argue that meaningful change in the representation, equity, and prestige of women faculty of color will require validating their experiences, supporting and valuing their research, creating opportunities for their professional recognition and advancement, and implementing corrective action for unjust assessment practices.